LncRNA HOXB-AS3 promotes proliferation, migration, and invasion of gallbladder cancer cells by activating the MEK/ERK pathway - Wu, Jiayan; Yu, Jiandong; Zhu, Hongquan; Chen, Zhiping; Liang, Yongling; Chen, Qin; Li, Guolin; Wan, Yunle (Heliyon, 2024)
LncRNA HOXB-AS3 are associated with tumor progression in several types of carcinomas, yet, its possibly biological role in gallbladder carcinoma(GBC) remains unclear. Therefore, this study aimed to investigate the biological function of HOXB-AS3 in GBC. To know the potential function of HOXB-AS3 in gallbladder carcinoma, real-time polymerase chain reaction was used to detected the expression of HOXB-AS3 in gallbladder carcinoma cells. The colony formation assay and cell counting kit-8 assay was performed to measured cell viability. Flow cytometry was to analyse cell apoptosis and cell cycle. Cell invasion and migration were determined by the transwell invasion assay and wound-healing assay. A nude mice xenograft tumor model was performed to investigate the biological function of HOXB-AS3 in vivo. The results indicated that HOXB-AS3 was significantly elevated in gallbladder carcinoma tissues and cell lines. We used siHOXB-AS3 to knockdown the expression levels of HOXB-AS3. And knockdown HOXB-AS3 expression depressed gallbladder cancer cell viability and induced cell apoptosis. In addition, the gallbladder carcinoma cell cycle was obviously arrested at the G1 phase. Cell invasion and migration were markedly suppressed following knockdown HOXB-AS3 expression. Furthermore, the features of siHOXB-AS3 in gallbladder cancer cells could be reversed by the ERK1/2 phosphorylation agonist Ro 67–7476. Finally, we confirmed that HOXB-AS3 promoted the growth of transplanted tumors in vivo. HOXB-AS3 promoted gallbladder carcinoma cell proliferation, invasion and migration by activating the MEK/ERK signaling pathway. HOXB-AS3 contributed to gallbladder cancer tumorigenesis and metastasis, making it a viable therapeutic target for gallbladder cancer treatment.